(3GdRjL GdeeJMf GdTQhGfi GdeYQha HGdeXaQis - (3HOQ GdOjf eMeO Hf CHj HcQ Hf eMeO GdaGQSjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ GdBjGJ ai YGde GdGfhGQ , hCOGQ GdCadGc djYde HgG ENJdGa Gddjd hGdfgGQ , hLYdgG LhGgQ TaGaI dGJMLH YeGhQGgG TjFkG dOhi GdCHUGQ s
(3BNQgG (B:s
(3hde jZjQhgG Yf ehGVYgG bahJ BKGQge hMcegG ai cd efRdI efgG aGage Pdc hgPg NGJeI CHhGH QSGFd gPG GdRjL GdeHGQc hGddg Gdehab s
(3cJH YfhGf GdcJGH ePgHkGs
(3hcJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3Gdadcs